General public takes up counterintuitive expert advice on effective climate action - Johannes Jarke-Neuert; Grischa Perino; Daniela Flörchinger; Manuel Frondel (Scientific Reports)
Abstract Individual voluntary climate action could contribute to closing the gap between global emission targets and the instruments in place. However, complex regulatory frameworks make it difficult for individuals to understand which actions align with their goals. Expert advice might provide guidance, but it is not trivial how detailed the advice should be. In a large consequential choice experiment with five informational load conditions, this paper uses the voluntary cancellation of European Union Allowances as an application to narrow down a minimum amount of information required to induce effective actions. We find a clear pattern of advice being processed and followed, even if it includes a demanding level of detail and counters prior convictions. Moreover, a mere assertion is highly effective already. These results are good news for efforts to increase the effectiveness of voluntary climate action.